2016
DOI: 10.1039/c6ta01781a
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplated hierarchical polyaniline composite electrodes with high performance for flexible supercapacitors

Abstract: A bioinspired structure flexible supercapacitor device with excellent electrochemical capacitance directly through a replica technique using natural resources has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…As displayed in Figure f, the HCM–0.05PANI-based SSC retained about 98.5% of the initial specific capacitance after 3000 cycles and a gentle reduction of the capacitance to 90.6% after 10 000 cycles, just a little bit less than that for HCM, indicating an excellent cycling stability. The cycling stability of HCM–PANI was comparable or better than that of many reported carbon–PANI composite-based cells. The improved cycling stability mainly benefited from three factors: the continuously interconnected carbon nanofiber structure allows fast movement of ions inside the whole electrode; homogeneous PANI nanoclusters uniformly deposited over the carbon nanofibers efficiently reduced the volume expansion of PANI caused by the doping/dedoping process; and uniformly doped nitrogen and oxygen of HCM offered favorable hydrophilicity to benefit the stable deposition of PANI and prevented PANI from falling off during the charge–discharge process. SEM images of HCM–0.05MPANI after 10 000 cycles are presented in Figure S12.…”
Section: Results and Discussionmentioning
confidence: 89%
“…As displayed in Figure f, the HCM–0.05PANI-based SSC retained about 98.5% of the initial specific capacitance after 3000 cycles and a gentle reduction of the capacitance to 90.6% after 10 000 cycles, just a little bit less than that for HCM, indicating an excellent cycling stability. The cycling stability of HCM–PANI was comparable or better than that of many reported carbon–PANI composite-based cells. The improved cycling stability mainly benefited from three factors: the continuously interconnected carbon nanofiber structure allows fast movement of ions inside the whole electrode; homogeneous PANI nanoclusters uniformly deposited over the carbon nanofibers efficiently reduced the volume expansion of PANI caused by the doping/dedoping process; and uniformly doped nitrogen and oxygen of HCM offered favorable hydrophilicity to benefit the stable deposition of PANI and prevented PANI from falling off during the charge–discharge process. SEM images of HCM–0.05MPANI after 10 000 cycles are presented in Figure S12.…”
Section: Results and Discussionmentioning
confidence: 89%
“…All CV curves show a broad oxidation and reduction peak ascribed to the pseudocapacitive behavior of PANI. These broad peaks are associated with the conversion of leucomeraldine to emeraldine and emeraldine to pernigraniline forms of PANI [59][60][61]. It is observed that the area under CV curves increased from P-1 to P-3 and it is maximum for P-3.…”
Section: Resultsmentioning
confidence: 91%
“…The wings were correctly replicated as can be seen in Figure 2, although pores in the structure were reduced and ridges achieved a serpentine shape compared to the original template [25]. Mycelium pellets [122] and polyalanine [123] have also been used to prepare useful materials for the production of supercapacitor devices.…”
Section: Energy Capture and Storagementioning
confidence: 91%